Protein degradation in rat skeletal muscle : intracellular, non-lysosomal enzyme systems and their endocrine control - Ismail, Firhaad (Division of Medical Biochemistry and Structural Biology, 2018)
Two manuscripts based on the work reported in this thesis were submitted and accepted for publication, the abstracts of which follow: SOLUBLE AND PARTICULATE FORMS OF MUSCLE ALKALINE PROTEINASE SHOW DIFFERENTIAL SENSITIVITY TO ENDOGENOUS INHIBITOR(S): Firhaad Ismail and Wieland Gevers, (Biochemistry International, In Press). Membrane-free washed myofibrils derived from rat skeletal muscle homogenates contained a chymostatin-sensitive protease(s) which acted on associated myofibrillar proteins, at an optimum pH of 8.5, much less rapidly at low ionic strength (insoluble myofilaments) than at high salt concentrations (solubilized proteins). When the myofibrillar fraction was added to the particle-free cytosol prepared from the muscle extracts, proteins of the cytosol were also degraded, but the activity in this case was much more pronounced at low ionic strength. This was because inhibitor(s) of the proteinase present in the cytosol fraction were only effective at high ionic strength when all the myofibrillar (and associated) proteins were in solution. The protease was separated from the bulk of the myofibrillar proteins by gel chromatography at high ionic strength. On dialysis against a low-salt buffer, part of the enzyme was precipitated. The putative cytosolic inhibitor(s) were again only effective on the soluble enzyme at high ionic strength. A HIGH MOLECULAR WEIGHT CYSTEINE ENDOPEPTIDASE FROM RAT SKELETAL MUSCLE: Firhaad Ismail and Wieland Gevers, (Biochim. Biophys. Acta, In Press). A cytosolic enzyme of high molecular weight (about 500000), which attacks native or denatured proteins (inter alia casein, globin and hexokinase) was purified about 1000-fold from mixed rat skeletal muscles, including muscles freed of mast cells by prior treatment of the animals with the degranulator, compound 48/80. Peptides of varying size were generated from radio-actively labelled globin, but no free amino acids were formed; free tyrosine was also not released from azocasein. The pH optimum was 7.5 and the presence of an essential cysteine group was suggested because dithiothreitol (1 mM) stimulated the activity and N-ethylmaleimide (5 mM) and p-chloromercuriphenylsulphonic acid (1 mM) were inhibitors. The activity was markedly inhibited by Zn²⁺ but not by leupeptin, chymostatin or pepstatin. The enzyme was stabilized by ATP, at concentrations as low as 0.1 mM, against inactivation at 42°C. The endopeptidase was clearly separated on gel chromatography from another large protease, also sensitive to Zn²⁺, but with marked aminopeptidase activity and the properties of Hydrolase H. The activity levels of the protease, assayed after chromatography on Sepharose 68 of high-speed supernatant fractions, did not vary significantly in skeletal muscle samples which were derived from denervated, starved, diabetic or hyperthyroid animals, in all of which the abnormal physiological states expressed themselves as enhanced rates of tyrosine release by incubated soleus and extensor digitorum longus muscles. Nevertheless, the enzyme described here may be part of an ATP-dependent, multi-component proteolytic system similar to that already known to be present in reticulocytes.